2020
DOI: 10.3390/pharmaceutics12020149
|View full text |Cite
|
Sign up to set email alerts
|

Topical Amphotericin B Semisolid Dosage Form for Cutaneous Leishmaniasis: Physicochemical Characterization, Ex Vivo Skin Permeation and Biological Activity

Abstract: Amphotericin B (AmB) is a potent antifungal successfully used intravenously to treat visceral leishmaniasis but depending on the Leishmania infecting species, it is not always recommended against cutaneous leishmaniasis (CL). To address the need for alternative topical treatments of CL, the aim of this study was to elaborate and characterize an AmB gel. The physicochemical properties, stability, rheology and in vivo tolerance were assayed. Release and permeation studies were performed on nylon membranes and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 55 publications
(59 reference statements)
1
25
0
5
Order By: Relevance
“…The use of antifungals for local use is also a necessity since, in addition to cutaneous fungal infections, there are diseases such as leishmaniasis where dermal application is also effective 34,35 . Some recent research has focused on developing new topical formulations of amphotericin B 36‐38 ; however, due to its lipid solubility, there is a possibility it can still be absorbed and produce systemic toxic effects. AmB‐A21, therefore, might also be usefully employed for cutaneous fungal infections at low doses.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antifungals for local use is also a necessity since, in addition to cutaneous fungal infections, there are diseases such as leishmaniasis where dermal application is also effective 34,35 . Some recent research has focused on developing new topical formulations of amphotericin B 36‐38 ; however, due to its lipid solubility, there is a possibility it can still be absorbed and produce systemic toxic effects. AmB‐A21, therefore, might also be usefully employed for cutaneous fungal infections at low doses.…”
Section: Discussionmentioning
confidence: 99%
“…Berenguer and coworkers present results on a ''Topical Amphotericin B (AmB) Semisolid Dosage Form for Cutaneous Leishmaniasis: Physicochemical Characterization, Ex-Vivo Skin Permeation and Biological Activity" [6]. The study describes an AmB gel that proved to be stable for 60 days at 4 • C and showed characteristics that made it favorable for cutaneous application.…”
mentioning
confidence: 99%
“…Extraction of the skin as a whole or distinct layers allows the evaluation of drug disposition profiles a methodology frequently used to compare drug distribution profiles of distinct formulations. 33,86 Besides the drugs highlighted above, topical formulations incorporating natural extracts have also been exploredsome displaying promising results in in vivo CL models. [87][88][89] It is important to note that commonly encountered problems such as (i) batch-to-batch variability of the extract, which may contribute to formulation and instability issues, (ii) availability of the plant material in sufficient quantities, and (iii) difficulties to identify the antileishmanial active molecule(s) compromise translatability and downstream development processes.…”
Section: Drug Development and Formulationmentioning
confidence: 99%